An active ingredient from the combination of Corydalis Rhizoma and Paeoniae Radix Alba relieves chronic compression injury-induced pain in rats by ameliorating AR/Mboat2-mediated ferroptosis in spinal cord neurons - Ze-Ming Wang; Xiao-Hong Wei; Gui-Yang Xia; Lin-Nan Zhou; Jin-Yu Li; Sheng Lin (Frontiers in Pharmacology)
IntroductionA combination of Corydalis Rhizoma (the dried tuber of Corydalis yanhusuo W.T. Wang) and Paeoniae Radix Alba (the root of Paeonia lactiflora Pall.) has been traditionally employed for analgesia. However, the underlying pharmacological mechanisms have not been clarified. The aim of the present study was to investigate the anti-inflammatory and analgesic effects of YB60, the 60% ethanol elution fraction derived from the combination of Corydalis Rhizoma and Paeoniae Radix Alba, and the explore the underlying mechanism.MethodsLipopolysaccharide-induced cellular inflammation model and chronic compression injury (CCI) rat model were used to study the anti-inflammatory and analgesic effects of YB60. Proteomics and molecular biology experiments were applied to explore the potential analgesic mechanism of YB60.ResultsThe results demonstrated that YB60 significantly decreased inflammatory cytokine levels both in cellular models and rat serum, while concurrently elevating pain thresholds in CCI rats. Proteomic analysis indicated that YB60 could upregulate the expression of Membrane Bound O-Acyltransferase Domain Containing 2 (Mboat2), a newly confirmed marker of ferroptosis. Furthermore, YB60 prevented ferroptosis in the spinal cords of CCI rats. Western blotting and immunofluorescent dual staining further revealed that YB60 increased the expression of Mboat2 and its upstream signaling molecule Androgen receptor (AR). Results in PC12 cells in vitro showed that YB60 reversed the downregulation of AR and Mboat2, and ameliorated ferroptosis induced by Erastin, while knockdown of AR eliminated the above effects of YB60.ConclusionThese findings indicated that YB60 exerted its analgesic effect by inhibiting ferroptosis in spinal cord neurons via modulation of the AR/Mboat2 pathway.